High-Resolution Head CTA: A Prospective Patient Study Comparing Image Quality of Photon-Counting Detector CT and Energy-Integrating Detector CT - Diehn, Felix E.; Zhou, Zhongxing; Thorne, Jamison E.; Campeau, Norbert G.; Nagelschneider, Alex A.; Eckel, Laurence J.; Benson, John C.; Madhavan, Ajay A.; Bathla, Girish; Lehman, Vance T.; Huber, Nathan R.; Baffour, Francis; et al. (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Photon-counting detector CT (PCD-CT) is now clinically available and offers ultra-high–resolution (UHR) imaging. Our purpose was to prospectively evaluate the relative image quality and impact on diagnostic confidence of head CTA images acquired by using a PCD-CT compared with an energy-integrating detector CT (EID-CT).MATERIALS AND METHODS: Adult patients undergoing head CTA on EID-CT also underwent a PCD-CT research examination. For both CT examinations, images were reconstructed at 0.6 mm by using a matched standard resolution (SR) kernel. Additionally, PCD-CT images were reconstructed at the thinnest section thickness of 0.2 mm (UHR) with the sharpest kernel, and denoised with a deep convolutional neural network (CNN) algorithm (PCD-UHR-CNN). Two readers (R1, R2) independently evaluated image quality in randomized, blinded fashion in 2 sessions, PCD-SR versus EID-SR and PCD-UHR-CNN versus EID-SR. The readers rated overall image quality (1 [worst] to 5 [best]) and provided a Likert comparison score (-2 [significantly inferior] to 2 [significantly superior]) for the 2 series when compared side-by-side for several image quality features, including visualization of specific arterial segments. Diagnostic confidence (0–100) was rated for PCD versus EID for specific arterial findings, if present.RESULTS: Twenty-eight adult patients were enrolled. The volume CT dose index was similar (EID: 37.1 extpm 4.7 mGy; PCD: 36.1 extpm 4.0 mGy). Overall image quality for PCD-SR and PCD-UHR-CNN was higher than EID-SR (eg, PCD-UHR-CNN versus EID-SR: 4.0 extpm 0.0 versus 3.0 extpm 0.0 (R1), 4.9 extpm 0.3 versus 3.0 extpm 0.0 (R2); all P values < .001). For depiction of arterial segments, PCD-SR was preferred over EID-SR (R1: 1.0–1.3; R2: 1.0–1.8), and PCD-UHR-CNN over EID-SR (R1: 0.9–1.4; R2: 1.9–2.0). Diagnostic confidence of arterial findings for PCD-SR and PCD-UHR-CNN was significantly higher than EID-SR: eg, PCD-UHR-CNN versus EID-SR: 93.0 extpm 5.8 versus 78.2 extpm 9.3 (R1), 88.6 extpm 5.9 versus 70.4 extpm 5.0 (R2); all P values < .001.CONCLUSIONS: PCD-CT provides improved image quality for head CTA images compared with EID-CT, both when PCD and EID reconstructions are matched, and to an even greater extent when PCD-UHR reconstruction is combined with a CNN denoising algorithm.CNNconvolutional neural networkCNRcontrast to noise ratioCTDIvolvolume CT dose indexEIDenergy-integrating detectorHUHounsfield unitIRiterative reconstructionICCintraclass correlation coefficientPCDphoton-counting detectorQIRquantum iterative reconstructionQrquantitative regularSRstandard resolutionUHRultra–high resolutionVMIvirtual monoenergetic image